Catalytic pyrolysis of biomass impregnated with elements from steelmaking slag leaching and simultaneous fabrication of phosphorus adsorbent. (15th December 2021) - Kan, Tao; Strezov, Vladimir; Evans, Tim; Kumar, Ravinder; He, Jing; Zhou, Xiaoteng; Ren, Jiawei; Lu, Qiang
Abstract: Energy shortage and environmental pollution are global concerns for sustainable development, which can be improved by high value-added reuse of solid wastes. In this study, a novel strategy was proposed for reusing steelmaking slag to treat biomass and produce valuable products. The study consisted of: i) useful elements (mainly Ca and Fe) were extracted from steelmaking slag through leaching then doped onto pine as catalysts for biomass pyrolysis; and ii) the produced slag elements (SE)@char was employed as adsorbent for P removal from wastewater. Results showed that compared to raw pine, SE@pine released more CO2 and CO due to the decomposition of formed calcium citrate on particles and the reaction of carbon with CO2 . In the bio-oil product from SE@pine, under the assistance of slag elements, the selectivity of total phenolic compounds dropped by half with the nitrogenous and acid groups showing the same descending trend, while the selectivity of alcohols and ketones increased. The slag elements, especially Ca and Fe, acted as catalysts for upgrading the bio-oil quality through enhancing the dehydration and dehydroxylation reactions. X-ray powder diffraction analysis indicated the presence of nano-size calcite particles on SE@char products from different pyrolysis temperatures. The SE@char from pyrolysis at 750 °C was attempted as adsorbent for phosphorus removal from aqueous solution. A phosphate adsorption capacity of 109 mg/g adsorbent was identified at the investigated conditions. The adsorption kinetics could be best described by the Elovich model, indicating the chemical reaction nature of the adsorption. This study explored the use of steelmaking slag and biomass wastes in a novel way for simultaneous production of upgraded biofuels and adsorbent for phosphorus control in wastewater. Graphical abstract: Image 1 Highlights: Pine was doped with elements from slag leaching and then pyrolysed at 500–750 °C. Slag elements enhanced CO production at temperature higher than 700 °C. Slag elements induced less acids and nitrogenous compounds in bio-oil. Biochar doped with slag elements had maximum P adsorption capacity of 109 mg/g.